A new Planothidium species (Achnanthidiaceae, Bacillariophyceae) from Xingu Ria, Amazon River basin, Brazil - Morais, Krysna S.; Costa, Lívia F.; Bicudo, Carlos E. De M.; Ector, Luc; Wetzel, Carlos E. (Phytotaxa, 2020)
A new Planothidium species was found in sediment samples (~4,000 yr BP) from the Xingu Ria (Xingu River), Brazilian Amazon. The new species morphology was analyzed using light and scanning electron microscopy. Planothidium xinguense sp. nov., is mainly characterized by its elliptical, slightly asymmetrical valves, with strongly marked short rostrate ends in the small specimens, while long and strongly rostrate apices are observable in the larger valves. The taxon belongs to the group of species bearing a cavum on the rapheless valves around the name “Planothidium rostratum sensu lato”. Morphology and ecology of the new species is compared with that of morphologically related taxa. Information of core chronology and the co-occurrence of other diatom species in the sample is also provided.